2007
DOI: 10.1108/14714170710754722
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking construction technology transfer in Thailand

Abstract: In an effort to more rapidly develop their infrastructure, economies and living standards, many newly industrialized countries, such as Thailand, have embarked on a series of international Technology Transfer (TT) initiatives within the construction and other industries. However, these initiatives have not immediately translated into enhanced capabilities and competitiveness within indigenous firms, resulting in a sustained reliance on foreign firms. With few clues as to why TT ventures have not created expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…KM is also a popular and growing research theme in Australia with several authors writing in this journal over the period, including contributions from Professor Peter Love (Edwards et al , 2005) from Curtin University and Assistant Professor Rodney Stewart (Stewart and Waroonkun, 2007; Waroonkun and Stewart, 2008; Panuwatwanich et al , 2009; Suprun and Stewart, 2015) from Griffith University being contributors to this journal together with many others from Australian Universities.…”
Section: Illustrating Km Research Focus Through Three Research Clustersmentioning
confidence: 99%
“…KM is also a popular and growing research theme in Australia with several authors writing in this journal over the period, including contributions from Professor Peter Love (Edwards et al , 2005) from Curtin University and Assistant Professor Rodney Stewart (Stewart and Waroonkun, 2007; Waroonkun and Stewart, 2008; Panuwatwanich et al , 2009; Suprun and Stewart, 2015) from Griffith University being contributors to this journal together with many others from Australian Universities.…”
Section: Illustrating Km Research Focus Through Three Research Clustersmentioning
confidence: 99%
“…The study showed that most firms operating worldwide are not using integrated global strategies effectively. Stewart and Waroonkun (2007) presented a TT performance measurement framework with eight different perspectives. Waroonkun and Stewart (2008) presented a model for international TT with the four factors including, government influence, transferee characteristics, transferor characteristics and relationship building.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A similar type of benchmark is developed in Hong Kong that identifies best practice measures of construction time performance for use by clients, consultants and contractors in the construction industry (Chan and Chan, 2004). Stewart and Waroonkun (2007) and Lau et al (2005) present academic studies on benchmark tools for the construction sector. Transparency International describes initiatives in several other countries that aim at improving the transparency in the construction sector (www.transparency.org/news_room/in_focus/2006/construction#readings).…”
Section: Introductionmentioning
confidence: 99%
“…Transparency International describes initiatives in several other countries that aim at improving the transparency in the construction sector. See the website: http://www.transparency.org/news_room/in_focus/2006/construction#readings 4 For academic studies on benchmark tools for the construction sector, see for example Stewart and Waroonkun (2007) and Lau et al (2005). 5 In this respect we would note that the interests, on an aggregate level, of project developers, constructors and advising engineering companies are fairly similar and can therefore all be accommodated within the category of "executing parties".…”
mentioning
confidence: 99%